Classification of factors affecting the formation and development of social infrastructure - Kolosivskyi, Nazarii (Human Geography Journal, 2025)
The classification of the factors of formation and development of the social infrastructure of a region is carried out according to certain criteria: origin, nature, direction, duration, manageability, level of occurrence, significance, focus, consequences. By origin, two main groups of factors are distinguished – natural-geographical and societal, with their further division into hierarchical lower-level units, namely subgroups of factors: economic, social, demographic, political, legal, managerial, financial, innovative, urban planning, infrastructural, cultural, personal. Their specifics are considered, namely: essence, composition, features of influence, significance, etc. Natural-geographical factors include geological structure, relief, soil cover, surface and groundwater, climate, flora and fauna, minerals and other natural resources. This group of factors significantly affects the formation of certain lifestyle standards, and it also determines the features of the location of social infrastructure facilities. Among economic factors, the following stand out: the socio-economic development of a region, the level and structure of employment, income differentiation, and the level of consumption of goods and services. A subgroup of social factors includes lifestyle characteristics, occupational distribution of the population, the amount and ways of spending free time, and so on. Population size, natural and mechanical movement, age and gender structure, the ratio of urban to rural residents, the proportion of the working-age population, etc. constitute a subgroup of demographic factors. The choice of priorities for the development of social infrastructure is significantly influenced by political factors. Legal factors play an important role in regulating the activities of social infrastructure facilities. When setting goals and developing regional development programs, managerial factors are crucial. A subgroup of innovative factors is associated with scientific and technological progress. Urban planning factors influence the location, type and scale of social infrastructure. Infrastructural factors refer to the state of the existing infrastructure in a region. A subgroup of cultural factors forms the system of spiritual and moral values of society, its customs and traditions. Personal factors are associated with the individual characteristics of each person. All factors have a specific impact on the territory and should be taken into account when planning the development of social infrastructure.